2018
DOI: 10.3389/fimmu.2018.02527
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin Prevents Lipopolysaccharide (LPS)-Induced Parkinson's Disease via Regulation of the AKT/GSK3β-Nrf2/NF-κB Signaling Axis

Abstract: Parkinson's disease (PD) is a common neurodegenerative disease characterized by selective loss of dopaminergic neurons in the substantia nigra (SN). Neuroinflammation induced by over-activation of microglia leads to the death of dopaminergic neurons in the pathogenesis of PD. Therefore, downregulation of microglial activation may aid in the treatment of PD. Polydatin (PLD) has been reported to pass through the blood-brain barrier and protect against motor degeneration in the SN. However, the molecular mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 56 publications
2
78
0
Order By: Relevance
“…Mounting studies have reported that LPS treatment inhibited the phosphorylation of Akt and GSK3- β in rat models of Parkinson's disease [26]. Our western blot and immunofluorescent results indicated that LPS treatment disrupts the survival pathway, demonstrated by a decrease in the expression and phosphorylation of Akt and GSK3- β proteins compared to saline-treated adult rats.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…Mounting studies have reported that LPS treatment inhibited the phosphorylation of Akt and GSK3- β in rat models of Parkinson's disease [26]. Our western blot and immunofluorescent results indicated that LPS treatment disrupts the survival pathway, demonstrated by a decrease in the expression and phosphorylation of Akt and GSK3- β proteins compared to saline-treated adult rats.…”
Section: Resultsmentioning
confidence: 50%
“…With respect to neuroinflammation, it has been suggested that several mechanisms are involved in the secretion of proinflammatory cytokines by astrocytes and microglial cells. One such mechanism is the LPS-induced p-JNK pathway that functions as a link between ROS/oxidative stress and neuroinflammation-mediated apoptotic neurodegeneration [4, 26, 37, 38]. It is well known that dietary curcumin is a strong candidate for the prevention of ROS/oxidative stress-mediated neuroinflammation-related neurodegeneration [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Akt pathways have been reported to be major players in the expression of numerous proinflammatory genes. Seldom reports demonstrated that activation of the Akt signaling pathway by LPS can induce the release of proinflammatory cytokines, and Huang et al's animal experiments showed that LPS did not activate Akt phosphorylation significantly in rats. But in the front part of our experiment, we found LPS could downregulate the expression of p‐Akt in C6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of LPS-induced PD, polydatin ameliorated motor dysfunction and protected dopaminergic neurons through the decrease of microglial activation and pro-inflammatory mediators. Furthermore, the levels of p-Akt and Nrf-2 were increased and the activation of NF-κB was suppressed by polydatin in the substantia nigra (Huang et al, 2018).…”
Section: Glycosylated Resveratrol Derivativesmentioning
confidence: 95%